Localization of hepatitis B core antigens in chronic active hepatitis using immunoperoxidase and chromotrope aniline blue staining. - Ozeki, T. (1987)
Hepatitis B (HB) core particle, in biopsied liver specimens from patients with chronic active hepatitis (type B) were stained with immunoperoxidase and chromotrope aniline blue (a non-immunological method) and the following results were obtained. HB core particles were more clearly stained with chromotrope aniline blue than with immunoperoxidase. Numerous HB core particles were seen not only in the nuclei of hepatocytes but also in the cytoplasm in HBeAg seropositive patients with severe chronic active hepatitis. DNAase digestion indicated that the HB core particles which stained with immunoperoxidase and chromotrope aniline blue contained DNA. Small amounts of HB core particles were seen in both the nuclei and cytoplasm of all anti-HBe seropositive patients with either moderate or severe chronic active hepatitis.